Influence of spin casting solvent on the self‐assembly of silicon‐containing block copolymer thin films via high temperature thermal treatment. Issue 4 (13th January 2022) - Giammaria, Tommaso J; Laus, Michele; Chiarcos, Riccardo; Ober, Christopher K; Seguini, Gabriele; Perego, Michele
Abstract: The present paper focuses on the influence of different solvents (toluene, mesitylene, acetone, tetrahydrofuran, propylene glycol monomethyl ether acetate (PGMEA) and ethyl acetate) on the self‐assembly behaviour of cylinder‐forming polystyrene‐ block ‐poly(dimethylsiloxane‐ random ‐vinylmethylsiloxane) diblock copolymer films deposited on thin brush layers of polystyrene (PS) or polymethylmethacrylate (PMMA) polymers grafted to a silicon substrate. The morphology and the key metrics for all samples were determined from the analysis of the SEM images and their evolution was investigated, as a function of the annealing time at 310 °C, for each solvent and for both PS and PMMA brushes. In general, shorter correlation lengths ξ are observed on PS brushes than on PMMA brushes. In addition, SEM data analysis reveals that tetrahydrofuran, PGMEA and ethyl acetate solvents promote a morphological change from fingerprint‐like parallel cylinders to a hexagonally packed dot pattern for annealing time t A > 30 s. Finally, the line edge roughness and linewidth roughness values are weakly dependent on both the casting solvent and the nature of the grafted brush. The reported data reveal that the choice of the polymer brush nature and of the solvent employed during the spin coating of the diblock copolymer film could substantially affect the self‐assembly process and requires accurate optimization due to their subtle interplay. © 2021 Society of Industrial Chemistry. Abstract : High correlation length values have been obtained for PS‐ b ‐P(DMS‐ r ‐VMS) (PS, polystyrene; DMS, dimethylsiloxane; VMS, vinylmethylsiloxane) thin films spin coated on polymethylmethacrylate (PMMA) brush layers by high temperature (310 °C) thermal treatments. A morphological change from fingerprint‐like parallel cylinders to a hexagonally packed dot pattern has been observed in PS‐ b ‐P(DMS‐ r ‐VMS) thin films spin coated on PS or PMMA brush layers.